PENGARUH PENGETAHUAN KESEHATAN GIZI DENGAN VIDEO ANIMASI TERHADAP PERSEPSI BODY IMAGE REMAJA PUTRI DI KELAS 2 SMP NEGERI 3 KABUPATEN BIREUEN - Husniati; Ferinawati (Jurnal Medicare, 2025)
Body image is commonly experienced by teenagers, with a prevalence reaching 71%. In Ireland, 26% of teenagers report feeling dissatisfied or very dissatisfied with their bodies, or having a negative body image. This issue is more prevalent among female adolescents compared to males. This study aims to examine the effect of nutritional health education using animated videos on the body image perception of female adolescents in Class 2 at SMP Negeri 3 Bireuen District. The research design used is a pre-experimental design with a one-group pretest-posttest approach. The study population consists of all female adolescents in Class 2 at SMP Negeri 3 Bireuen, with the sampling technique employing the total population, totaling 34 respondents. The Wilcoxon test results show that 91.2% of respondents had good knowledge (α = 0.05), with a p-value (0.000) < α (0.05), meaning that Ha is accepted and Ho is rejected. The study concludes that there is a significant effect of nutritional health education using animated videos on the body image perception of female adolescents. This research is expected to encourage respondents to actively participate in improving positive body image perception among female adolescents.